The impact of bacillus pumilus TS2 isolated from yaks on growth performance, gut microbial community, antioxidant activity, and cytokines related to immunity and inflammation in broilers - Guo, Chuangen; Liu, Sirui; Di, Liangjiao; Tang, Shu (Frontiers in Veterinary Science, 2024)
Intensive poultry farming faces challenges like gut inflammation in the absence of antibiotics, resulting in reduced productivity, heightened susceptibility to enteric diseases, and other complications. Alternative strategies are needed to manage inflammation and maintain sustainable poultry production. Yaks living in high-altitude hypoxic environments have specialized gut microbes. However, yak probiotics remain largely uncharacterized. We previously isolated a strain of Bacillus pumilus (named TS2) from yaks and demonstrated its potential as a probiotic in vitro. Therefore, in this study, we evaluated the in vivo growthpromoting, antioxidant, immune, and anti-inflammatory effects of Bacillus pumilus isolated from yaks in broilers. We demonstrated the safety of TS2 isolated from yaks in broilers.Furthermore, we found that TS2 increased the average daily weight gain (ADWG) and reduced the feed conversion ratio (FCR). Supplementation with TS2 also improved the mucosal morphology, the ratio of villi to crypt cells, and enzyme activity. High-throughput sequencing showed that the abundance of Lactobacillus was higher in the TS2 treated broilers. Importantly, the serum level of malondialdehyde (MDA) was reduced and the levels of total antioxidant capacity (T-AOC) and superoxide dismutase (SOD) activity were increased in the low-dose TS2 group, while the inflammatory factors interleukin-1β (IL-1β), interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) were downregulated compared with the control group. We demonstrated that TS2 supplementation can increase the overall growth performance and ameliorate the blood parameters related to inflammation and immunity in broilers.